Pemanfaatan Lingkungan sebagai Sumber Belajar pada Mata Pelajaran IPA Kelas III di Madrasah Ibtidaiyah Negeri 21 Jakarta - Indrawati Indrawati; Supardi Supardi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the utilization of the surrounding environment (compost) as a learning resource in the subject of science for grade III at MIN 21 Jakarta TimurDistrict. The researcher used a qualitative method with a descriptive approach. The researcher collected data through observation, interviews and documentation related to the utilization of organic waste as a learning resource or learning media conducted with grade III teachers at MIN 21 Jakarta TimurDistrict. The results of the study showed that the utilization of the surrounding environment (compost) namely the use of compost as a learning resource can improve students' process skills in science subjects. Through the utilization of compost, students are more active in learning outdoors because it is more fun, students can also see directly what is being learned if they use real sources that are in the school environment. It is important to remember that students' learning preferences and levels of understanding can vary. Some students may be more responsive to this learning method, while others may need a different learning approach. Here are some recommendations for the utilization of the surrounding environment (compost) as a learning resource in science subjects, namely about the benefits of compost and experiments in making compost.